2011
DOI: 10.3389/fnhum.2011.00017
|View full text |Cite
|
Sign up to set email alerts
|

Mental Training as a Tool in the Neuroscientific Study of Brain and Cognitive Plasticity

Abstract: Although the adult brain was once seen as a rather static organ, it is now clear that the organization of brain circuitry is constantly changing as a function of experience or learning. Yet, research also shows that learning is often specific to the trained stimuli and task, and does not improve performance on novel tasks, even very similar ones. This perspective examines the idea that systematic mental training, as cultivated by meditation, can induce learning that is not stimulus or task specific, but proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
220
0
12

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(252 citation statements)
references
References 91 publications
20
220
0
12
Order By: Relevance
“…Comparably, more extensive research shows that engaging in meditation practice results in improved cognitive performance, which is associated with changes in brain activity indicative of improved neural efficiency (Chiesa et al 2011;Lutz et al 2008;Malinowski 2013;Slagter et al 2011). The cognitive enhancement observed in these studies by and large reflects far transfer because effects are found in tasks that are very different to what is practiced during MM.…”
Section: Mindfulness Meditation and Cognitive Skill Trainingmentioning
confidence: 99%
“…Comparably, more extensive research shows that engaging in meditation practice results in improved cognitive performance, which is associated with changes in brain activity indicative of improved neural efficiency (Chiesa et al 2011;Lutz et al 2008;Malinowski 2013;Slagter et al 2011). The cognitive enhancement observed in these studies by and large reflects far transfer because effects are found in tasks that are very different to what is practiced during MM.…”
Section: Mindfulness Meditation and Cognitive Skill Trainingmentioning
confidence: 99%
“…The attention training component of mindfulness has already been identified and studied as a separate component that demonstrates "the benefits of being present" (e.g., Brown & Ryan, 2003;Slagter, Davidson, & Lutz, 2011;Wadlinger & Isaacowitz, 2011). Little research, however, has systematically investigated the perspectival component of mindfulness that focuses on "the benefits of simply observing."…”
Section: Conceptualizing Mindfulness In Future Research and Applicationsmentioning
confidence: 99%
“…As a form of mental training, meditation has an advantage over other types of skills training in changing neural structure and functioning (Slagter, Davidson, & Lutz, 2011). Meditation, and other forms of mental training, do not rely on external stimuli, but instead rely on the mental simulation of core cognitive and emotional processes that support a wide range of related skills (Slagter et al, 2011). This propensity for meditation-induced changes in neural processes to support skills that transfer to novel areas of one's life provides one powerful mechanism through which meditation can induce lasting behavioral and emotional changes.…”
Section: Meditationmentioning
confidence: 99%